Truly emergent? A critique of ‘third space’ in cross-cultural context - Michael Begun (Journal of Learning Development in Higher Education)
The aim of this piece is to critique Celia Whitchurch’s influential third space theory in cross-cultural context. Whitchurch first describes third space in a 2008 paper as an ‘emerging landscape of activity’ (p. 378) correlative with an ‘emergence of Third Space professionals’ (p. 377) in first world anglophone higher education institutions. By theorising the emergence of third space from the activity of these so-called ‘third space professionals’, Whitchurch implicitly relies upon a concept first developed several decades earlier in cultural theory. Most notably, Homi K. Bhabha discusses his own conception of third space in response to questions about his ground-breaking 1988 essay ‘The commitment to theory’, in which he appears to first introduce the term ‘third space’ in a relevant context. Problematically, however, there appear to be substantial inconsistencies between Whitchurch’s and Bhabha’s third space theories. The three most significant of these are: 1) the key distinction, introduced by Bhabha, between cultural difference and cultural diversity; 2) the broader concepts of identity and identification upon which Whitchurch and Bhabha rely; and 3) their respective relations to the history of colonialism and corresponding commitments to divergent neo-colonial and postcolonial projects. Based on these discrepancies, I contend that, whereas Bhabha’s third space seems truly cross-culturally emergent, Whitchurch’s third space only appears to be so within a more limited cultural context. Accordingly, I conclude by proposing two further ways in which learning developers should uphold the commitment to a critical cross-cultural approach.